O campo em revista: agrarismo e modernismo no Estado do Rio de Janeiro nos anos de 1920 - Paiva, Evelyn Morgan Monteiro (2014)
The present research investigates how the countryside was portrayed in the 1920s by the intellectuals from Rio de Janeiro Fluminense region. By analyzing three magazines –Illustração Fluminense (1921-1924), A Agricultura Fluminense: revista da Sociedade de Agricultura e Indústrias Ruraes (1926) and A Fazenda Fluminense (1929- 1930) – we aim to understand how the countryside alternatively paved the way to the modernization carried out in the State of Rio de Janeiro. The magazine was a media genre that symbolized modernity, producing new sensitivities and behaviors during a period of transformations. Fluminense economy had been undergoing a crisis since late nineteenth century, leading the State to play a walk-on parting the national republican politics. The aforementioned agricultural magazines analyzed hereby were willing to rebuild this Fluminense identity by proposing modernized field crops with new farming techniques together with agricultural diversification policies, counting on investments in agricultural education and small property planning. The countryside, often acknowledged as 'underdeveloped', integrated the modernist Fluminense proposals at the beginning of the twentieth century.